Primary care experience and remission of type 2 diabetes: a population-based prospective cohort study. (12th September 2020) - Dambha-Miller, Hajira; Day, Alexander; Kinmonth, Ann Louise; Griffin, Simon J
Abstract: Background: Remission of Type 2 diabetes is achievable through dietary change and weight loss. In the UK, lifestyle advice and referrals to weight loss programmes predominantly occur in primary care where most Type 2 diabetes is managed. Objective: To quantify the association between primary care experience and remission of Type 2 diabetes over 5-year follow-up. Methods: A prospective cohort study of adults with Type 2 diabetes registered to 49 general practices in the East of England, UK. Participants were followed-up for 5 years and completed the Consultation and Relational Empathy measure (CARE) on diabetes-specific primary care experiences over the first year after diagnosis of the disease. Remission at 5-year follow-up was measured with HbA1c levels. Univariable and multivariable logistic regression models were constructed to quantify the association between primary care experience and remission of diabetes. Results: Of 867 participants, 30% (257) achieved remission of Type 2 diabetes at 5 years. Six hundred twenty-eight had complete data at follow-up and were included in the analysis. Participants who reported higher CARE scores in the 12 months following diagnosis were more likely to achieve remission at 5 years in multivariable models; odds ratio = 1.03 (95% confidence interval = 1.01–1.05, P = 0.01). Conclusion: Primary care practitioners should pay greater attention to delivering optimal patient experiences alongside clinical management of the disease as this may contribute towards remission of Type 2 diabetes. Further work is needed to examine which aspects of the primary care experience might be optimized and how these could be operationalized.